Smart Dumpster: Design Of Tracking Dump Truck And Monitoring Of Waste Places To Support Effectiveness Of Waste Transportation In Bandung City (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The waste problem is a problem that has not been appropriately resolved, especially in various regions in Indonesia, with the increasing number of people in big cities, which is directly proportional to the production of waste produced. If the community does not handle the waste transportation process correctly, it will cause waste accumulation, especially at the TPA. Waste management must pay more attention to waste management, especially regarding cost efficiency and environmental quality. With the development of technology, it is necessary to change and develop waste better by utilizing information technology. Mobile applications are an option so that a system can be accessed anywhere and anytime. The community hopes that this mobile-based system can help waste transporters get information quickly and accurately. Therefore, in this research, the Smart Dumpster application will be carried out.Researchers built this smart dumpster application using the waterfall methodology, where the process starts from defining needs, designing software, implementing to the system testing process. This application uses a mobile application and the Android platform by utilizing Google Maps technology. This technology is integrated with a trash can detection system by providing information about the waste height status when the trash is filled.The results obtained to create a smart dumpster system make it easier for waste transporters to determine which Garbage dump to visit for the transportation process without visiting all Garbage dump one by one.